The Functional Impact of VX-770 on the Cystic Fibrosis Transmembrane Conductance Regulator Is Enduring and Increases the Constitutive Activity of This Channel in Primary Airway Epithelia Generated from Healthy Donors - Heidi J. Nick; Sarah E. Christeson; Preston E. Bratcher (Biomolecules)
VX-770 is a small-molecule CFTR potentiator that is highly efficacious in individuals with cystic fibrosis caused by mutations in CFTR that result in a defect in channel gating. While studies have reported on the mechanism of action of VX-770, there is still more to learn about the impact that it has on CFTR function in various contexts. The aim of the present study was to examine the longevity and stability of the effect of VX-770 on CFTR function in cultured airway epithelia and to measure the consequences of this interaction. The responses to acute and chronic VX-770 exposure were measured in cultures of expanded and re-differentiated primary human nasal epithelial cells. Acute VX-770 exposure resulted in an increase in CFTR-mediated currents in the absence of exogenous compounds that induce the phosphorylation/activation of CFTR, with acute exposure having the same effect as chronic exposure. The functional impact of VX-770 on CFTR was long-lasting in cultured airway epithelia, as they maintained an electrophysiological profile consistent with the saturation of CFTR with VX-770 over time periods of up to 4 days following a short (0.5 min) or low-dose (100 nM) exposure to VX-770 during an analysis in an Ussing chamber. Rinsing the apical surface prior to VX-770 exposure or exposure during the analysis in the Ussing chamber increased the interaction between VX-770 and the CFTR. Importantly, after short, low-dose exposures to VX-770, the CFTR channels in cultured epithelia appeared to remain saturated with VX-770 for extended periods of time, despite the repetitive rinsing of the apical surface. This finding has implications for patients discontinuing the use of VX-770-containing therapies.